Kepuasan Kerja dan Komitmen Organisasional: Pengaruhnya Terhadap Intensi Keluar - Purna, I Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; Volume.02.No.12.Tahun 2013, 2013)
Job satisfaction is a major determinant of organizational commitment and intention turnover . This study aimed to determine the effect of job satisfaction and organizational commitment to intention turnover . Using a 105 sample from a 412 population , with a response rate of 97.14 % obtained the data as much as 102 questionnaires that had been completed . Collected data were analyzed by Structural Equation Modelling ( SEM) using smart PLS sofware. The results showed that a significant positive effect of job satisfaction on organizational commitment and negarif significant effect on the intention turnover . Similarly, commitment organisional is significant negative effect on intention turnover . The implications of this study is must be maintain the level of intention turnover by increasing job satisfaction to be increased organizational commitment . Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;}
Keywords: work satisfaction, organizational commitment, intention turnover.